Completion lower lobectomy after basal segmentectomy for pulmonary sclerosing pneumocytoma with lymph node metastasis. Issue 11 (11th November 2021) - Komatsu, Hiroaki; Izumi, Nobuhiro; Tsukioka, Takuma; Inoue, Hidetoshi; Ito, Ryuichi; Nishiyama, Noritoshi
Abstract: A 20-year-old man was referred to our hospital because of a tumor in his left lung. Chest computed tomography showed a 35-mm nodule in the left lower lung lobe. Bronchoscopic examination and cryobiopsy were performed, which revealed suspicion for sclerosing pneumocytoma. We performed basal segmentectomy, and intraoperative-frozen pathological examination revealed no metastases in the segmental lymph nodes. However, the postoperative pathological diagnosis revealed metastasis in these nodes. We performed additional resection of segment 6 (completion lower lobectomy) and hilar and mediastinal lymph node dissection 2 weeks after the first surgery. The postoperative course was favorable, and the patient was discharged 13 days after the second surgery. Pathological examination of the additional resected specimens revealed lymph node metastases in the interlobar and mediastinal lymph nodes. Pulmonary sclerosing pneumocytoma with lymph node metastasis is extremely rare, and its prognosis is unclear. Recurrence has been reported rarely, and long-term follow-up is required.